Why is the Corporation Tax Not Neutral? Anticipated Tax Reform, Investment Spurts and Corporate Borrowing - Luis Alvarez JR; Vesa Kanniainen; Jan Södersten (Uppsala University, Department of Economics, 2000)
The paper shows that a corporate tax policy which is thought to be neutral may have significant incentive effects. This result is established in a model with tax advantage to debt and expectations about a forthcoming tax reform. Investment spurt effects are established and compared to those of a firm with equity finance. A tax-cut cum base-broadening tax reform which leaves the long-run investment incentives of an all-equity firm unaffected is shown to cause a substantial short run investment hike. The findings are illustrated by numerical simulations indicating the magnitudes of the spurt effects.
urn:nbn:se:uu:diva-2478
Keywords: H25; H32; 330; Tax neutrality; Tax reform; Investment spurts; Debt finance; Körperschaftsteuer; Besteuerungsprinzip; Steuerreform; Erwartungstheorie; Investition; Unternehmensfinanzierung; Theorie